CRISPR-Cas9: A Story of Discovery, Innovation, and Revolution in Genome Editing - Hermantara, Rio (Indonesian Journal of Life Sciences, 2024)
CRISPR-Cas9 is a powerful and flexible genome editing technology that has transformed the field of life sciences. It enables the creation and modification of genomic sequences of various organisms, with wide-ranging implications for biotechnology, agriculture, and medical research. The origin of CRISPR as an adaptive immune system in bacteria, the elucidation of CRISPR-Cas9 biological and molecular mechanisms, and the subsequent engineering and optimization of it as a programmable genome editing tool are remarkable achievements in science. In this review, we will summarize this fascinating history and also explore the recent innovations of the CRISPR-Cas9 system, which extend the genomic tool box to improve the accuracy and efficiency of genome editing.